Profil Pemasaran Produk Koperasi di Kalimantan Selatan (Kasus pada 48 Koperasi yang Diperingkat Tahun 2011) - Suarniki, Ni Nyoman (Universitas Brawijaya, Indonesia, 2015)
This research aims to know the result of cooperation rank at South Kalimantan in2011 and to find out the marketing profile of products of cooperation as one of the indicatorsof activities and progress for cooperation. The respondents on this research are the administratorsfrom 48 cooperations in which ranked in 2011; the data collected by questionnaires,observations and un-structured interviews. Data analysis is using descriptive analysis.Based on the ranking result, there are 20 cooperations that have a good quality rankand 28 cooperatives that have medium quality rank. Most of the cooperations are onlyinvolved in lending and borrowing business, only few of them are involved in other types ofbusiness. There were not been any significant effort in order to improve the target market;market is limited for members only. Promotion efforts relatively did not exist. It is assumedthat this condition is due to that most administrators of cooperative only consider cooperationsas a side-job, as well as lack of skills and competencies on the administrators ofcooperative. Hence, it still requires a lot of attention. Government support has not yet beenoptimally used. We suggested that the administrators need to pay more attention to thedevelopment and progress of their cooperations and to utilize various assistances and supportsfrom government through cooperation department on the provincial/regency/city level.